DAMPAK CROWD NOISE TERHADAP KINERJA DAN PENGAMBILAN KEPUTUSAN WASIT PADA KOMPETISI LIGA ASKOT U-12 SEMARANG: STUDI KUALITATIF DENGAN PENDEKATAN NARATIF - Danuarta, Candra; Nurrachmad, Limpad (Universitas Hamzanwadi, 2025)
This study was motivated by the phenomenon of psychological pressure experienced by young referees due to crowd noise in early age soccer matches, particularly in the Semarang U-12 Askot League. The noise from the spectators is thought to affect the emotional stability, concentration, and decision-making accuracy of referees who are still in the developmental stage. The purpose of this study is to explore in depth the impact of crowd noise on performance and the adaptive strategies developed by young referees. The method used is qualitative narrative, involving seven young referees and seven head coaches as participants. Data were collected through semi-structured interviews, observations, and noise measurements using the Decibel X application, then analyzed thematically with NVivo 15. The results revealed that crowd noise caused emotional pressure (nervousness, hesitation) and cognitive impairment (decreased focus, inaccurate decisions). Referees developed coping strategies such as self-talk and concentration, but these strategies were not fully effective. In conclusion, crowd noise significantly affects the performance of young referees, requiring integrated emotional regulation and stress management training in referee development, as well as sportsmanship education for all stakeholders involved in the game.